Pengunaan Formula Haversine pada Sistem Informasi Pencarian Guru Mengaji - Faisal Faisal; Nahrun Hartono; Muhammad Syafei (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2021)
The search for private reciting teachers is mainly carried out through contacts with colleagues of the same profession, recommendations from previous reciting teacher service users so that broadcasts through social media problems that then arise through searches like this, including searching for prospective private reciting teachers who take a long time, find it challenging to find a match The location and time between the prospective Koran Kaji and the students, cannot know the competence, achievements and track-records of the future Koran teachers in private. This research is qualitative research where the strategy used is Design and Creation—the method used for data collection using the form of observation, literature study, questionnaires and interviews. This research aims to design a system that can make it easier for students to find Koran teachers. In contrast, the design of this system uses the Java and MySQL programming languages for databases and the programming method using the Haversine Formula method. This research produces an Android-based private apprenticeship teacher information system application for the conclusions drawn from this study. To design a system for ordering private Koran teachers to make it easier for the community, especially in Makassar.